ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA AUDIO VISUAL POKOK BAHASAN SINTESIS PROTEIN UNTUK SMA - Ima Nurani (Jurnal VARIDIKA, 2016)
The aim of this study is to obtain 1) description of the use of learning media as teaching resource on biology learning process that has been happening in the field 2) the views and constraints faced by teachers in the field for delivering protein synthesis subject. 3) formulation of learning media that needs to be developed on biology learning of protein synthesis subject. The observation result was in the form of teacher’s needs assessment instrument that analyzed using descriptive qualitative obtained that the use of learning media as teaching resource on biology learning process that has been happening in the field has not done optimally. There are constraints in delivery of material, especially material that cannot be observed directly or abstract. 2) The protein synthesis subject is a difficult subject, in its delivery, teachers need media that can visualize the process of protein synthesis for twelfth grade and explain it in detail and correctly so there is no misconception of students towards protein synthesis subject. 3) The learning media that needs to be developed in biology learning of protein synthesis subject is in the form of audio-visual media.